PENGARUH PERSEPSI ASAL NEGARA (COUNTRY OF ORIGIN) TERHADAP NIAT BELI YANG DIMEDIASI CITRA MEREK - Putra, Ida Bagus Oka Keswara; Suprapti, Ni Wayan Sri (E-Jurnal Manajemen; Vol 8 No 8 (2019), 2019)
This research was conducted in Denpasar City with a total sample of 110 samples. Determination of the sample using non-probability sampling method, namely purposive sampling. Methods of collecting data using non-behavioral observations and questionnaires. The analysis technique used is path analysis technique. Based on the results of the research conducted, it was found that perceptions of national origin had a positive and significant effect on brand image, this means that the better the perception of national origin of Oppo would improve the Oppo brand image. Perceptions of national origin have a positive and significant effect on purchase intentions. This shows consumers 'perceptions of perceptions of national origin influence consumers' buying intention towards Oppo smartphone products. Brand image has a positive and significant effect on purchase intention. This shows that the Oppo brand image has a significant influence on consumers' purchase intentions. Brand image is able to mediate the influence of perceptions of national origin on purchase intention, this means that the brand image mediates the influence of perceptions of national origin into the overall purchase intention. Keywords: perception of national origin, brand image, purchase intention